Silent pneumomediastinum after salmon ingestion -A clinical dilemma - Pramod Chirakkal (14777380) (2020)
Esophageal perforation caused by accidental swallowing of foreign bodies in adults is a rare challenging emergency. Especially when the fish bone causing the perforation has been dislodged from esophagus and is missing in the images. We experienced such a case in an adult male patient who had perforated esophagus after unintentional ingestion of a salmon fish bone. The patient visited our emergency department complaining of difficulty in swallowing for 4 hours. A review of history revealed that he consumed a salmon fish 4 h ago. A plain x-ray soft tissue neck revealed suspicion of mediastinal air tracking and Computed tomography (CT) of neck confirmed the hyper dense concentric wall thickening of the upper esophageal lumen at the level of thoracic inlet and pneumomediastinum seen surrounding the trachea, esophagus, bilateral hilar region extending superiorly in to the neck, posterior to the right common carotid artery and inferiorly up to and surrounding the distal esophagus, also pneumomediastinum more pronounced around the level of aortic arch and below the thoracic duct. Conservative medical management was done with help of thoracic surgeon and discharged after 3 days with full recovery. Other Information Published in: Otolaryngology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.xocr.2020.100226